Acute white matter changes following sport‐related concussion: A serial diffusion tensor and diffusion kurtosis tensor imaging study. Issue 11 (6th October 2016) - Lancaster, Melissa A.; Olson, Daniel V.; McCrea, Michael A.; Nelson, Lindsay D.; LaRoche, Ashley A.; Muftuler, L. Tugan
Abstract: Recent neuroimaging studies have suggested that following sport‐related concussion (SRC) physiological brain alterations may persist after an athlete has shown full symptom recovery. Diffusion MRI is a versatile technique to study white matter injury following SRC, yet serial follow‐up studies in the very acute stages following SRC utilizing a comprehensive set of diffusion metrics are lacking. The aim of the current study was to characterize white matter changes within 24 hours of concussion in a group of high school and collegiate athletes, using Diffusion Tensor and Diffusion Kurtosis Tensor metrics. Participants were reassessed a week later. At 24 hours post‐injury, the concussed group reported significantly more concussion symptoms than a well‐matched control group and demonstrated poorer performance on a cognitive screening measure, yet these differences were nonsignificant at the 8‐day follow‐up. Similarly, within 24‐hours after injury, the concussed group exhibited a widespread decrease in mean diffusivity, increased axial kurtosis and, to a lesser extent, decreased axial and radial diffusivities compared with control subjects. At 8 days post injury, the differences in these diffusion metrics were even more widespread in the injured athletes, despite improvement of symptoms and cognitive performance. These MRI findings suggest that the athletes might not have reached full physiological recovery a week after the injury. These findings have significant implications for the management of SRC because allowing an athlete to return to play before the brain has fully recovered from injury may have negative consequences. Hum Brain Mapp 37:3821–3834, 2016 . ©2016 Wiley Periodicals, Inc .